Hubungan Tingkat Stres dengan Social Media Self Disclosure pada Mahasiswa - Yunalia, Endang Mei; Haryuni, Sri; Samudera, Wahyu Sukma; Hawiyah, Siti (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2024)
The burden faced by students during lectures can cause stress. The stress faced by students requires students to find ways to deal with stress. One method used by students is to vent negative feelings in the form of stress on social media or what is called social media self-disclosure. The aim of this research is to determine the correlation between stress levels and social media self-disclosure in students. This research is a correlational analytical research using a cross sectional approach. The population in this study were students at the Faculty of Health Sciences, namely 429 students with a total research sample of 207 respondents selected using proportional random sampling techniques. The research results showed that the majority of respondents with mild levels of stress had moderate social media self disclosure, namely 109 respondents (52.6%). The statistical test results of the relationship between stress levels and social media self-disclosure in students using the spearman rank correlation test showed that p-value = 0.000 α = 0.05, which means there is a relationship between stress levels and social media self-disclosure in students. The correlation coefficient value obtained is 0.379 which can be interpreted as meaning that the relationship between stress levels and social media self-disclosure in students has a weak correlation with a positive relationship direction, which means that the higher the stress level, the higher the level of social media self-disclosure. Students should be able to use social media appropriately to reduce the stress they face.